Reviewing the Market Stability Reserve in light of more ambitious EU ETS emission targets - Sebastian Osorio; Oliver Tietjen; Michael Pahle; Robert Pietzcker; Ottmar Edenhofer (ZBW – Leibniz Information Centre for Economics, 2020)
The stringency of the EU's Emission Trading System (ETS) is bound to be ratcheted-up to deliver on more ambitious goals as put forth in the EU's Green Deal. Tightening the cap needs to consider the interactions with the Market Stability Reserve (MSR), which will be reviewed in 2021. Against that background, we employ the detailed model LIMES-EU to analyse options for the upcoming reforms. First, we examine how revising MSR parameters impacts allowance cancellations through the MSR. We find that under current regulation, the MSR cancels 5.1 Gt of allowances. Varying MSR parameters leads to cancellations in the range of 2.6 and 7.9 Gt, with the intake/outtake thresholds having the highest impact. Intake rates above 12% only have a limited effect but cause oscillatory intake behaviour. Second, we analyse how the 2030 targets can be achieved by adjusting the linear reduction factor (LRF). We find that the LRF increases MSR cancellations substantially (up to 10.0 Gt). This implies that increasing the LRF from currently 2.2% to 2.6% could already be consistent with the 55% EU-wide emission reduction target in 2030. However, we highlight that the number of MSR cancellations is subject to large uncertainty. Overall, the MSR increases the complexity of the market. In face of that, we suggest to develop the MSR into a Price Stability Reserve.
Keywords: L94; Q58; 330; EU climate policy; EU ETS reform; linear reduction factor (LRF); Market Stability Reserve (MSR); EU ETS Phase IV